Solvent and spin state effects on molecular structure, IR spectra, binding energies and quantum chemical reactivity indices of deferiprone–ferric complex: DFT study. (15th October 2016) - Kaviani, Sadegh; Izadyar, Mohammad; Housaindokht, Mohammad Reza
Graphical abstract: The solvent and spin state effects on the molecular structure of Fe(DFP)3, by DFT calculations have been performed at the CAM-B3LYP/6-31G(d) level of theory. The binding energies in high-spin and in the presence of the solvent are higher than intermediate- and low-spin states. Abstract: In this work, in order to determine the solvent and spin state effects on the molecular structure of deferiprone–ferric complex ([Fe(DFP)3 ]), density functional theory (DFT) calculations were performed at the CAM-B3LYP/6-31G(d) level of the theory. The results indicate that the stability and binding energy of [Fe(DFP)3 ] in the polar solvents are higher and lower, respectively, than non-polar ones. The analysis of the spin state energies of the complexes showed that the corresponding stability constants increase with the spin states increment. The binding energies in high-spin state is higher than intermediate- and low-spin states which showed that the complex formation in a high-spin state is more favorable. Furthermore, the evaluation of the IR spectrum in the various solvents reveals that the intermolecular hydrogen bond formation between the oxygen atom of the carbonyl group and the hydrogen atom of the solvent causes a spectral red shift. Because of the importance of the charge transfer in the complex formation, donor–acceptor interaction energies were evaluated. Based on this analysis, lone pair electrons of the oxygen atom interact with the antibonding orbitals of the iron, more than the other possibilities. Finally, some probable correlations between the quantum chemical reactivity indices of the complexes and solvent polarity were considered. According to the obtained results, an enhancement in the dielectric constant of the solvent decreases the electrophilicity index while the electronic chemical hardness increases. Recent study indicates a linear correlation between chemical hardness and binding energies of [Fe(DFP)3 ] complex.